(untitled) - Chowdhury, G. G. (London, 2008)
The book designs the phenomenon of developments in IT, especially the World Wide Web, have led to the creation of a number of digital library research projects in the UK, USA and elsewhere. The design and development of digital libraries depend on computer, communication and other technical skills, and the dream of successful digital libraries leading to a global digital environment can only be fulfilled when enough practitioners have the skills to design, build and manage them. Designed to present a holistic view of the digital library scene, this text is based on evidence from examples of major digital library research projects around the globe. It is intended for students of digital librarianship and related courses at departments of information science and computer science in the UK and worldwide, and also for practitioners and researchers who need to get a good grasp of issues and developments in the field
Keywords: Digital libraries,Thư viện số